The Role of Enterprise Risk Management, Intellectual Capital, and Sustainability Report in Enhancing Firm Value: Profitability as a Moderator in Indonesian Pharmaceutical Companies (2017–2023) - Mailini, Dini; Gursida, Hari; Sasongko, Hendro (Asosiasi Ahli Administrasi Indonesia, 2025)
This study examines the effect of Enterprise Risk Management, Intellectual Capital, and Sustainability Report on firm value, with profitability measured by Return on Assets as a moderating variable. The research is motivated by the increasing importance of non-financial disclosure in assessing firm value, particularly in high-risk industries such as pharmaceuticals. The objective of this study is to evaluate whether Enterprise Risk Management, Intellectual Capital, and Sustainability Report contribute significantly to firm value and whether profitability enhances this relationship. The research was conducted on pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the period 2017 to 2023. This study applied a quantitative approach using panel data regression to analyze direct relationships and moderated regression analysis to assess the moderating effect. The findings indicate that Enterprise Risk Management, Intellectual Capital and Sustainability Report each have a positive and significant impact on firm value. However, none of these variables shows a significant effect on profitability. Furthermore, return on assets demonstrates a positive and significant influence on firm value, but does not moderate the relationship between Enterprise Risk Management, Intellectual Capital, and Sustainability Report with firm value. These results suggest that although non-financial indicators such as enterprise risk management, intellectual capital, and sustainability reporting are critical in enhancing market valuation, they do not automatically translate into short-term financial performance, nor are their impacts conditioned by profitability levels. The study highlights the importance of aligning non-financial strategies with financial performance to ensure long-term value creation.